FAKTOR-FAKTOR YANG DAPAT MEMPENGARUHI ASSET GROWTH PADA PERUSAHAAN MANUFAKTUR SEKTOR FARMASI YANG TERDAFTAR DI BEI - Nuni Sari; Mohamad Husni (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2021)
the purpose of this study is to determine the  influence of firm size on asset growth and debt to equity ratio prices on asset growth prices and simultaneously between return on asser and debt to equity ratio on asset growth prices. The research method used is quantitative. With the number of populations and samples as many as 9 companies with 5 observation periods, the number of data used as much as 45 data from the multiplication of 9 banks x 5 years observation period. The test result of the first hypothesis (H1)is known signification value = 0.014 is smaller than at 0.05 or sig value < 0.05, then Ha  received H0  is rejected. The test result of the second hypothesis (H2)is known to signify = 0.691 greater than at 0.05 or sig value > 0.05, then Ha  rejected H0  is accepted. The results of the third hypothesis test (H3)are known  Fcount  = 5034 and Ftable  = 2.89 so Fcalculates>Ftable with a significant level above 0.05 i.e. 0.13. Based on the results of hypothesis testing can be concluded that  firm size affects the price of asset growth and debt to equity ratio has no effect on the price of asset growth and simultaneously between firm size and debt to equity ratio affects assetgrowth